Pengaruh Gaya Kepemimpinan Transformasional dan Motivasi Kerja Terhadap Kinerja Dosen pada Sekolah Tinggi Desain Indonesia di Bandung - Gabriella Oktaviana Sitompul; Asep Kurniawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Lecturer performance is a crucial factor in determining a higher education institution's success in improving the quality of education, research, and community service. Sekolah Tinggi Desain Indonesia (STDI) Bandung is one of the private higher education institutions required to ensure that its lecturers perform optimally in carrying out the Tri Dharma of Higher Education. Based on preliminary observations, lecturer performance has not yet reached an optimal level, as indicated by the low achievement in research and community service activities, as well as the less-than-optimal level of lecturer attendance. This study aims to examine the effect of transformational leadership and work motivation on lecturer performance, both partially and simultaneously. This research employed a quantitative method using multiple linear regression analysis and the coefficient of determination with the assistance of SPSS version 26. Data were collected through questionnaires distributed to all 30 lecturers of STDI Bandung using a saturated sampling technique. The results show that transformational leadership has a significant partial effect on lecturer performance, while work motivation does not have a significant partial effect on lecturer performance. However, transformational leadership and work motivation simultaneously have a significant effect on lecturer performance. The coefficient of determination of 56.7% indicates that the variation in lecturer performance can be explained by transformational leadership and work motivation, while the remaining 43.3% is influenced by other factors not examined in this study.